Historiography of Ya.F.Chepyha’s Herritage - Natalya Bohdanets-Biloskalenko (Pedagogical Discourse, 2013)
The author of the article briefly presents historiography of the heritage of the outstanding Ukrainian pedagogue, scientist Yakov Feofanovych Chepyha. In general terms, his activities and those articles and writings, which referto the famous teacher, who was for a long timed hushed in the Soviet period, have been characterized. A few notes in vivo and a significant amount of researches since the time of independence have been mentioned. In terms of national school formation for the first time the attention is paid to Ilchenko M. (1995), and academician Sukhomlynska O. (1996). Over time, L.Berezivska handles legacy of the scientist-pedagogue and publishes in 2006 a collection of his works with the profound foreword. All these works became the basis for the further researches of  scientific and educational achievements of Ya. Chepyha.